A new species of Trachylepis (Squamata: Scincidae) from Central Africa and a key to the Trachylepis of West and Central Africa - Allen, Kaitlin E.; N., Walter P. Tapondjou; Welton, Luke J.; Bauer, Aaron M. (Zootaxa, 2017)
A new species of skink, Trachylepis gonwouoi sp. nov. is described from Cameroon and the Republic of the Congo. It differs from all other species of Trachylepis in Central-West Africa by a combination of number of keels on dorsal scales (3–5); moderate SVL (maximum size of 80 mm); number of scale rows at midbody (28–34); number of supracilliaries (6–10); a well defined lateral white stripe, bordered by black, extending from under the eye to the insertion of the hind limb; and a ventral color in life of bright blue-green. Trachylepis gonwouoi sp. nov. was found in association with disturbed forest at elevations from 50 to 1050m. This species is syntopic with T. affinis and T. maculilabris. In order to aid in the identification of Trachylepis in West and Central Africa with the addition of T. gonwouoi sp. nov., we provide an updated key to the Trachylepis found from Mauritania through the Democratic Republic of the Congo. This key combines previous literature that treated Western and Central African taxa separately and represents the most comprehensive key for Trachylepis in West-Central Africa to date.